2018
DOI: 10.21608/epsj.2018.23250
|View full text |Cite
|
Sign up to set email alerts
|

Using Natural and Synthetic Antioxidants in Low-Protein Diets to Improve the Performance of Broiler and Reduce Lost Nitrogen in Feces

Abstract: The objective of this study was to investigate the effects of using natural and synthetic antioxidants for improving growth performance, some blood parameters, manure characteristics and economical efficiency. A total number of 360 Ross breed chicks, two day old, were weighted and randomly distributed into six groups each of sixty birds; each group has three replicates each replicates has 20 birds which were allocated in individual pin. The experiment was approved at the same time following similar design. Fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…In this study, dietary supplementation with Pulicaria jaubertii improved the overall performance of broiler chickens, such as live weight, daily weight gain, feed conversion ratio, production efficiency index, and performance index compared to the control group during the study period. Elabd [ 34 ] found that dietary supplementation with pulicaria undulata powder as a medicinal plant (3 g/kg diet) gave the best results in the overall growth performance of broilers. This suggests that the effectiveness of dietary supplementation with Pulicaria jaubertii on growth performance may be due to the active compounds, fatty acids, and nutrients contained in it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, dietary supplementation with Pulicaria jaubertii improved the overall performance of broiler chickens, such as live weight, daily weight gain, feed conversion ratio, production efficiency index, and performance index compared to the control group during the study period. Elabd [ 34 ] found that dietary supplementation with pulicaria undulata powder as a medicinal plant (3 g/kg diet) gave the best results in the overall growth performance of broilers. This suggests that the effectiveness of dietary supplementation with Pulicaria jaubertii on growth performance may be due to the active compounds, fatty acids, and nutrients contained in it.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high fiber content of this plant may play a role in the lowest lipid levels [ 44 ]. Another study by Elabd [ 34 ] reported that this decrease in total cholesterol concentration could be due to the bioactive compounds of Pulicaria jaubertii , which are able to inhibit hepatic 3-hydroxy-3-methylglutaryl coenzyme A activity, an important regulatory enzyme in cholesterol synthesis. The results of our study showed that Pulicaria jaubertii had no effect on the relative weight of internal organs (thymus, bursa, spleen, heart, pancreas, and kidneys), while T2 and T3 increased the relative weight of the liver compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dietary feeding of Pulicaria undulata powder improved the body performance of broiler chickens ( Elabd, 2018 ). Also, Shirani et al (2019) found that broilers fed on Pulicaria powder had increased body weight gain with better FCR, attributed to its antioxidant effect and the positive impact on gut health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…PJ is an aromatic medicinal plant used as a spice, as a safe substitute for synthetic antioxidants, and for traditional treatment of humans [ 13 , 14 , 15 ]. It is rich in bioactive compounds such as flavonoids, terpenoids, and phenols, which can improve the performance and meat quality of broiler chickens [ 19 , 20 ]. The results obtained in this study show that production efficiency, as an indicator of economic performance, health, and welfare status of broiler chickens, was higher in diets supplemented with PJ powder, especially at 3 g PJ in the starter phase (1 to 10 days old), whereas dietary supplementation of 9 g PJ during the grower phase (11 to 24 days old) improved feed conversion compared to a non-supplemented basal diet but had no effect on other parameters of growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have been conducted with extracts of PJ, as they were found to have antioxidant properties due to their bioactive compounds [ 17 , 18 ]. The use of other aromatic plants as natural dietary supplements, such as Pulicaria gnaphalodes powder [ 19 ], Pulicaria undulata powder [ 20 ], and Eucalyptus globulus oil [ 21 ], has demonstrated that these bioactive compounds can enhance the performance and meat quality of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%